Peripheral neuropathy complicating pancreatitis and major pancreatic surgery. - Gross, M L (1988)
Four cases of a polyneuropathy associated with pancreatitis and pancreatic pseudocyst formation are reported. Electrophysiological investigation showed the peripheral neuropathy to be predominantly axonal in type. These patients were all seriously ill and many factors may have been involved in the pathogenesis of their neuropathy. They had all received parenteral nutrition and multiple drug therapy including metronidazole, and all had severe sepsis. There was evidence that insufficient vitamin replacement had been given during total parenteral nutrition. It was not possible to decide whether the polyneuropathy resulted from the summation of these factors, is similar to what has been called the polyneuropathy of the critically ill, or is a new association with pancreatic disease.